STREET POLITICS, DIGITAL ACTIVISM, AND DEMOCRATIC FUTURES: MEDIA DISCOURSES ON INDONESIA’S ROAD TO 2045 - Efendi, Zakaria; Meysella Al Firdha Hanim; Irwan Abdullah; Zaenuddin Hudi Prasojo; Maghfira Nur Aziza (Universitas Negeri Semarang, 2025)
This study analyzes the role of youth street politics in the dynamics of Indonesian democracy by emphasizing the integration of physical and digital spaces. Unlike previous studies that tend to separate street politics from digital activism, this study combines the two through a Critical Discourse Analysis (CDA) framework of national and international media coverage and reputable journal articles. The findings of this study show that youth street politics is no longer limited to physical action, but has transformed into a hybrid practice of participation that gains widespread resonance through digital amplification. Street politics functions as an arena for democratic correction while also being positioned as a threat to political stability, reflecting the ambiguity that continues to be produced in public discourse. Theoretically, this study contributes to strengthening the concept of hybrid democracy by showing that street politics is a medium of negotiation between state legitimacy, media representation, and digital community participation. Empirically, the study clarifies how digital connectivity changes the structure of mobilization and produces new meanings of civil resistance. Practically, these findings confirm that student street politics, if managed within a deliberative and participatory framework, has significant potential to strengthen the consolidation of Indonesian democracy towards 2045.